Development of Automatic Berthing Support Program for Autonomous Ships - Byung-Sun Kang; Chang-Hyun Jung; Keewon Kim; Hyunwoo Kim; Jin-Soo Kim; Dae-Hae Kim (Applied Sciences)
Research on autonomous ships has primarily focused on developing response technologies for navigation from pilot station to pilot station. This study developed an automatic berthing support program that calculates the necessary thruster output values for the bow and stern to achieve the desired berthing speed under varying external force conditions, requiring only essential ship information as input. The program determines the thruster output by analyzing the forces and moments acting on the hull during the berthing process. An experimental setup equipped with the automatic berthing support program was installed on a ship. The outputs of the bow thruster (Thruster(F)) and stern tug (Tug(A)) were 300–544 hp on average, whereas the values calculated by the automatic berthing program (Program(F), Program(A)) were 105–131 hp. The calculation results of the automatic berthing support program of the ship were approximately 3–5 times greater than the horsepower values of the thruster and tug used during actual berthing, probably because the actual berthing speed was 0.25–1.13 m/s, which is more than five times higher than the set speed of 0.05–0.15 m/s. The results indicate that the automatic berthing support program is promising for future applications in automatic berthing systems for autonomous ships.